Comorbidity in Patients with Dhat Syndrome: A Nationwide Multicentric Study. (22nd April 2015) - Grover, Sandeep; Avasthi, Ajit; Gupta, Sunil; Dan, Amitava; Neogi, Rajarshi; Behere, Prakash B.; Lakdawala, Bhavesh; Tripathi, Adarsh; Chakraborty, Kaustav; Sinha, Vishal; Bhatia, Manjeet Singh; Pattojoshi, Amrit; et al.
Abstract Introduction There are limited numbers of studies on Dhat syndrome. Major limitations of the existing literature are heterogeneous assessment methods used to describe the comorbidity and small sample size from isolated centers. Aim To assess comorbidity with a common methodology in patients with Dhat syndrome from multiple centers across India. Methods Using a cross‐sectional design, this multicentric study involved assessment of 780 male patients, aged more than 16 years, across 15 study centers. Main Outcome Measures ICD‐10 criteria (for evaluation of psychiatric morbidity and sexual dysfunction) Results About one‐third (32.8%) of the cases had no comorbidity. One‐fifth (20.5%) of the patients had comorbid depressive disorders and another one‐fifth (20.5%) had comorbid neurotic, stress‐related and somatoform disorders. Half (51.3%) of the study sample had comorbid sexual dysfunction. When various combinations of comorbidities were evaluated, it was seen that more than one‐fourth (28.7%) of the patients had only comorbid sexual dysfunction and one‐sixth (15.9%) had only comorbid depressive/anxiety disorders. A little more than one‐fifth (22.6%) had comorbidity of both sexual dysfunction and depressive/anxiety disorders. Conclusion Comorbid sexual dysfunction is seen in half of the cases of Dhat syndrome, and it is more common than comorbid depressive and anxiety disorders. Grover S, Avasthi A, Gupta S, Dan A, Neogi R, Behere PB, Lakdawala B, Tripathi A, Chakraborty K, Sinha V, Bhatia MS, Pattojoshi A, Rao TSS, and Rozatkar A. Comorbidity in patients with Dhat syndrome: A nationwide multicentric study. J Sex Med 2015;12:1398–1401.